2010
DOI: 10.5209/rev_laza.2010.v31.6
|View full text |Cite
|
Sign up to set email alerts
|

Relaciones entre los parámetros físico-químicos del suelo y la vegetación en juncales de Scirpoides holoschoenus

Abstract: Relaciones entre los pará-metros físico-químicos del suelo y la vegetación en los juncales de Scirpoides holoschoenus. Lazaroa 31: 99-107 (2010).Se ha llevado a cabo un estudio de la diversidad de juncales caracterizados por Scirpoides holoschoenus en la zona centro de la Península Ibérica (cuencas media y alta del río Tajo). Este estudio se basa en 54 inventarios fitosociológicos recogidos de la bibliografía y en 17 muestreos propios en los que se analizó la composición florística de la vegetación y los princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Previous studies on Scirpoides holoschoenus grasslands on a regional scale (Iberian Peninsula) revealed soil‐soluble ion content as a major driver of floristic composition (García‐Madrid et al. ). According to our analyses, this soil variable can be related to the lithological factor discriminating tall humid grasslands on base‐poor and sandy soils (groups 1–4) from grasslands on base‐rich habitats (groups 5–9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on Scirpoides holoschoenus grasslands on a regional scale (Iberian Peninsula) revealed soil‐soluble ion content as a major driver of floristic composition (García‐Madrid et al. ). According to our analyses, this soil variable can be related to the lithological factor discriminating tall humid grasslands on base‐poor and sandy soils (groups 1–4) from grasslands on base‐rich habitats (groups 5–9).…”
Section: Discussionmentioning
confidence: 99%
“…; García‐Madrid et al. ). Molinio‐Holoschoenion is also shaped by anthropogenic influences (Rey Benayas & Scheiner ), since pastoral systems contribute to maintaining its characteristics in the intermediate stages of vegetation succession (Moreira et al.…”
Section: Introductionmentioning
confidence: 97%
“…"30TVK75": "Cultivado en la vega de Perales de Tajuña, Izco (1969)". 30TVK85: [VK8258] Orusco de Tajuña, 610 m, García-Madrid et al (2010). 30TVL43: *Buitrago, Fernández (1988); Lozoyuela, arroyo de la Nava, Fernández (1988).…”
Section: Asparagus Officinalis Lunclassified